Development of system for study on human recognition influenced by changing button press sensation - Yasuhiro ONO; Yuji ISHINO; Takeshi MIZUNO; Masaya TAKASAKI (Mechanical Engineering Journal, 2025)
Recently, touch screens have been used to operate smartphones and personal computers. When touch panels are used to operate devices, somatosensory feedback cannot be enjoyed. This lack of somatosensory feedback increases the reliance on visual feedback to provide a sense of operation. This may reduce device operation performance. Therefore, it is necessary to gain a sense of operation through somatosensory feedback. However, the quantitative evaluation of the relationship between somatosensory feedback and the perception of button operation is still insufficient. The purpose of this study is development of a system to quantitatively investigate influence of the button press operation elements on its recognition by the somatic perception. In this paper, improvement of an experimental apparatus designed for the quantitative evaluation is reported. The apparatus consists of a voice coil motor, leaf springs, a displacement sensor, a force sensor and a key top and can control vertical displacement and force. The kinesthetic sensation of pressing a physical button can be emulated with the apparatus. The design of the voice coil motor was improved based on results of the numerical magnetic field analysis. Observation of improved response and additional improvement with feedback control are also mentioned. Trial presentation of button press sensation is described. To discuss influence of hysteresis characteristic in the profile, results of sensory test with thirty participants are also reported.